Application of polyaniline coated fiber bragg grating optical sensor for chloroform detection / Irma Zulayka Mohamad Ahad - Irma Zulayka , Mohamad Ahad (2017)
Fiber Bragg grating (FBG) optical sensor coated with polyaniline (PAni) was used for the detection of organic compounds. In this study, PAni was synthesized through chemical oxidation method by using aniline (Ani) as a monomer and ammonium persulfate (APS) as an initiator. Dioctyl sodium sulfosuccinate (AOT) was added as a dopant in order to increase the solubility and conductivity of PAni. The chemical structures of PAni were confirmed by Fourier transform infra-red (FTIR) and ultraviolet-visible (UV-Vis) spectra while the conductivity of PAni was determined using four-point probes measurement. In the preparation of optical sensor, FBG was first etched in the aqueous hydrofluoric acid solution (48 %) to remove the cladding layer and PAni was then coated on the FBG. Different organic compounds such as 1-propanol, 2-propanol, ethylenediamine, chloroform, dichloromethane, dimethyl sulphide (DMS) and dimethyl disulphide (DMDS) were detected by PAni coated FBG sensor using the optical sensor set up. The response of sensor was monitored based on the Bragg wavelength shift at ~1557 nm using optical spectrum analyzer (OSA). Among all organic compounds, the sensor possesses the highest Bragg wavelength shift (0.095 nm) in chloroform detection. Therefore, further studies in the optical sensor application are focused on chloroform detection. The sensitivity of sensor was manipulated by different synthesis parameters of PAni such as different AOT dopant ratios (Ani: AOT= 5: 3, 5: 5 and 5: 7) and different polymerization temperatures (25 °C, 0 °C and -5 °C). Among all PAnis, Ani:AOT = 5: 5 (0 °C) sensor was found to be the best in chloroform detection that showed good sensitivity (0.0015), good recyclability up to 10 times with fast response time (7 s) and recovery time (8 s), good linearity (0.9988) and lower detection limit of 9.22 ppm. The supporting data from FTIR, UV-vis and conductivity analysis suggested that the proposed mechanism for the interaction between PAni and chloroform is the dipole-dipole interaction (physical interaction) between the partial negative charge (Clδ-) of chloroform and the partial positive charge (NHδ+) of PAni.